ANALISIS PENGARUH KUALITAS LAYANAN DAN KUALITAS INFORMASI WEBSITE TERHADAP KUAITAS WEBSTE E-COMMERCE MENGGUNAKAN METODE WEBQUAL - Suryani, Dimitha Anggraeni Putri; Wibowo, Januar; Fianto, Achmad Yanu Alif (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
E-Commerce is often called an online trading is the process of deployment, purchasing, sales, marketing goods and services via the Internet between the consumer to consumer (C2C), or an agency to consumers (B2C). E-commerce increasingly widespread popular Indonesian society, a variety of emerging e-commerce led to competition between e-commerce becomes very tight. For an e-commerce website can survive in the competition, or in order to become a popular e-commerce websites, each e-commerce website should be able to have a quality website. Quality website will result in the increase of sales transactions of the e-commerce. This research was conducted to determine an e-commerce website that is qualified with the goal to analyze the influencerof thesquality of service and quality of website information on the quality of e-commerce websites. This study uses data collection techniques such as questionnaires and had obtained a sampled of 110 respondents. The process of analysisx usedt in this study is the beginning of the validity and reliability, followed by a multiplez regressiont analysish. The resultsk of thishstudy indicatemthat thed variable Service Quality does not affect the variable Website Quality whereas Information Quality significant and positive impact on the e-commerce Website Quality.